THE DIRECT SALE OF RAW MILK: PREVALENCE OF PATHOGENS IN RAW MILK AND BOVINE FAECES COLLECTED IN FARMS WITHIN THE PROVINCE OF PESARO-URBINO - A. Petruzzelli; D. Sola; F. Paolini; S. Baldassarri; N. Orazietti; M. Foglini; E. Micci; G. Pezzotti; T Cenci; F. Tonucci (Italian Journal of Food Safety, 2009)
In the last years, direct sale of raw milk by vending machines has largely increased in several European Countries and Italy. As a consequence, adequate hygienic measures and correct consumer’s information is required in order to reduce any potential risk linked to this product. In the present study, the occurrence of pathogens (Salmonella spp., verocytotoxigenic E.coli, Campylobacter spp., Listeria monocytogenes, S.aureus) in raw milk and bovine faeces collected in 4 farms in the province of Pesaro-Urbino (Italy), between January 2007 and March 2009 has been investigated; 99.5% of milk samples resulted negative for the pathogens considered and complying with the regulation S. aureus limits. Campylobacter has been found in 0.44% of the samples, collected during summer, while only one sample resulted positive to a non-verocytotoxigenic E.coli O157. In respect to faeces, 62.6% of the samples resulted negative, 33.6% were contaminated by Campylobacter spp. (68% Campylobacter coli and 32% Campylobacter jejuni) and 3.8% by E.coli O157. No samples resulted positive for Salmonella spp. or Listeria monocytogenes. The results highlight the necessity of a strict plan of hygienic and sanitary controls, with particular attention to milking process hygiene and raw milk storage, to reduce the risk of contamination of the product.